Peroral Endoscopic Myotomy for Esophageal Motility Disorders - Jun Young Kim; Yang Won Min (Korean Society of Gastrointestinal Endoscopy, 2020)
Peroral endoscopic myotomy (POEM) is one of the most clinically successful tunnel-based minimally invasive endoscopic treatments. The classic indications of POEM include achalasia of all types, including failed prior treatments, and expanded indications include the non-achalasia esophageal motility disorders, such as esophagogastric junction outflow obstruction, diffuse esophageal spasm, and jackhammer esophagus. For achalasia treatment, POEM has achieved a comparable surgical efficacy and a safety outcome and, therefore, has emerged as a first-line treatment. For non-achalasia esophageal motility disorders, POEM has also shown high clinical response rates. The complication rate of POEM for esophageal motility disorders is low and most complications are managed with conservative treatment. Currently, POEM is a representative procedure of natural orifice transluminal endoscopic surgery, which has shown a good clinical efficacy with low complication rates for esophageal motility disorders including achalasia. However, further studies are needed to treat non-achalasia motility disorder via POEM.